WTO disciplines on agricultural support: A comparison of India's WTO domestic support notifications with shadow measurements: WTO domestic support update - Gopinath, Munisamy (2012)
This is a WTO domestic support notification update prepared for the International Food Policy Research Institute (IFPRI) on the chapter for India in WTO Disciplines on Agricultural Support: Seeking a Fair Basis for Trade (Orden, David, David Blandford, and Tim Josling, editors), 2011, Cambridge: Cambridge University Press.